The Role of Tobacco-Derived Carcinogens in Pancreas Cancer. (17th July 2011) - Lochan, Rajiv; Reeves, Helen L.; Daly, Anne K.; Charnley, Richard M.
Abstract : The extremely poor outcome from pancreas cancer is well known. However, its aetiology less well appreciated, and the molecular mechanisms underlying this are poorly understood. Tobacco usage is one of the strongest risk factors for this disease, and this is a completely avoidable hazard. In addition, there are well described hereditary diseases which predispose, and familial pancreas cancer. We have sought here to summarise the role of tobacco-derived carcinogens and the mode of their tumorigenic action on the pancreas. There is compelling evidence from animal and human studies (laboratory including cell line studies and epidemiologic) that tobacco derived carcinogens cause pancreas cancer. However, the manner in which they do so is not entirely apparent. There is also compelling evidence that synergism with genetic and other life-style factors—like diet obesity—results in a multifactorial causation of the disease. Ascertaining the role of tobacco carcinogens in the development of this cancer and their interaction with other risk factors will enable novel therapeutic and preventative strategies to improve outcome from this appalling malignancy.